Cationic and Neutral (Ar‐BIAN)Copper(I) Complexes Containing Phosphane and Arsane Ancillary Ligands: Synthesis, Molecular Structure and Catalytic Behaviour in Cycloaddition Reactions of Azides and Alkynes. Issue 9 (14th January 2013) - Li, Lidong; Lopes, Patrícia S.; Figueira, Cláudia A.; Gomes, Clara S. B.; Duarte, M. Teresa; Rosa, Vitor; Fliedel, Christophe; Avilés, Teresa; Gomes, Pedro T.
Abstract: A series of new cationic and neutral (Ar‐BIAN)copper(I) complexes [in which Ar‐BIAN = bis(aryl)acenaphthenequinonediimine] was synthesised and characterised by elemental analysis, 1D and 2D NMR spectroscopy and single‐crystal X‐ray diffraction. The cationic complexes of the general formula [Cu(Ar‐BIAN)L 2 ]BF4 [L 2 = (PPh3 )2 (1 ), dppe (2 ), dppf (3 ), (AsPh3 )2 (4 ); Ar = 4‐ i PrC6 H4 (a ), 4‐MeOC6 H4 (b ), 4‐NO2 C6 H4 (c ), 2‐ i PrC6 H4 (d ), Ph2 PCH2 CH2 PPh2 (dppe), (Ph2 PC5 H4 )2 Fe (dppf)] were synthesised by reaction of [Cu(EPh3 )4 ]BF4 (E = P or As) and equimolar amounts of Ar‐BIAN ligands, or by reaction of equimolar amounts of [Cu(NCMe)4 ]BF4, 4‐ i PrC6 H4 ‐BIAN (a ) and diphosphanes dppe or dppf, in dichloromethane, whereas the neutral complexes of the types [CuX(Ar‐BIAN)(EPh3 )] [X = Cl, E = P (5 ); X = I, E = P (6 ); X = Cl, E = As (9 )] and [CuX(Ar‐BIAN)2 ] [X = Cl (7 ), I (8 ); Ar =a, b, c, d, 2, 4, 6‐Me3 C6 H2 (e ), 2, 6‐ i Pr2 C6 H3 (f )] were prepared by reaction of CuCl or CuI with equimolar amounts of Ar‐BIAN and EPh3 (E = P, As or Sb) in acetonitrile under reflux conditions. The type of ancillary ligand EPh3 and the aryl substituents on Ar‐BIAN play crucial roles in determining the formation of cationic or neutral copper(I) complexes. No copper(I) complexes containing coordinated SbPh3 were isolated; all the corresponding attempts led to dimeric complexes7 or8 . Most of the complexes crystallised easily. Their study by X‐ray diffraction revealed distorted‐tetrahedral geometries around the copper(I) centres, which are quite influenced by the various aryl substituents on Ar‐BIAN and the ancillary ligands EPh3 . All complexes1 –9 except cationic dppf derivative3a are active catalysts for cycloaddition reactions of alkynes and azides, and also show good tolerance towards functionalised substituents of alkynes and azides. Among them, the PPh3 ‐coordinated complexes1, 5 and6 afforded the highest catalytic activities [turnover frequency = 26.9–45.7 h –1 ]. Abstract : The synthesis and structural characterisation of new cationic and neutral (Ar‐BIAN)copper(I) [Ar‐BIAN = bis(aryl)acenaphthenequinonediimine] complexes containing phosphane and arsane ancillary ligands are described. Their behaviour as catalysts for cycloaddition reactions of alkynes and azides is presented.